Efficacy and safety of deferasirox in myelodysplastic syndromes - Breccia, Massimo; Alimena, Giuliana (Annals of hematology, 2013)
Transfusion dependence in myelodysplastic syndrome (MDS) patients may lead to organ damage due to accumulation of non-transferrin-bound iron with consequent increased oxidative stress. Iron chelation has been reported in retrospective studies to improve overall survival in low-risk MDS patients, but this information needs to be validated in prospective trials. The oral iron chelator, deferasirox, has been shown to reduce serum ferritin levels in chelation naïve and pre-treated patients and to reduce labile plasma iron, independently from the efficacy on iron overload. Deferasirox is a potent NF-kB inhibitor, tested in vivo and on acute myeloid leukemia and MDS cell lines, and this effect may explain in part the phenomenon of hematological improvements reported in case reports and in different clinical trials. The drug has an acceptable safety profile, with the most common side effects reported being non-progressive change in serum creatinine level, gastrointestinal disturbances, and skin rash. In this review, we report the results of different studies testing safety and efficacy of deferasirox in MDS patients, side effects associated with the drug, and suggested management of iron overload.